Female Foeticide Perceptions and Practices Among Women in Surat City - Nawal Shaikh; Hiral Viradiya; Dhwanee Thakkar; RK Bansal; Dhara Shah; Shashank Shah (Medsci Publications, 2011)
Female foeticide besides skewed sex ratio and its attendant social evils has grave ethical undertones, especially for medical professionals and our commitment to save lives. Randomly selected 270 women were interviewed using a semi-structured interview schedule to explore the female foeticide perceptions and practices among couples in Surat city. Only 148 (51.9%) of the women were aware of the fact that 3 female children killed every minute in India. Prenatal sex determination among their relatives and neighbours were reported by 80% respondent, though they themselves had never resorted to it. Could this figure influence the proxy rates for community behaviour, perhaps, this needs indepth exploration. Supporting to this fact, 25.9% respoindents reported of ever been pressurized by their family members to undergo prenatal sex diagnosis of their foetus. Encouragingly 90% respondents had opined that that repeated prenatal sex diagnosis and abortions are detrimental to the mental and physical health of a woman and is wholly preventable. Stricter laws and honest enforcement of these laws were the commonest suggestions by respondent to prevent female foeticide in society.